Fibre optic seismic sensor for down-well monitoring in the oil industry. (July 2018) - He, Xiangge; Pan, Yong; You, Hongjuan; Lu, Zhiwei; Gu, Lijuan; Liu, Fei; Yi, Duo; Zhang, Min
Highlights: A seismic monitoring system for steam-assisted gravity drainage (SAGD) wells has been demonstrated. The sensing fiber cables are installed not only in observation wells but also in producer wells and injector wells. The vibration signals in observation wells and producer wells are both obtained. This seismic monitoring system is a useful tool in SAGD well monitoring applications. Abstract: Steam-assisted gravity drainage (SAGD) technology is highly promising for heavy oil and extra heavy oil reservoirs exploitation. Proper monitoring of the SAGD process is essential to improve production efficiency and avoid operational issues. Among all the monitoring techniques, seismic monitoring can provide useful information about the steam-chamber development. In this paper, we demonstrate a seismic monitoring system based on dual-pulse heterodyne demodulation technique, of which the structure is very simple and easy to be installed into downhole. Field trials have been conducted in Xinjiang Oilfield, China. The results validate the performance of the system and indicate its applicability in SAGD process monitoring.